Negotiating Work-Life Balance in the Digital Age: A Phenomenological Study of Remote and Hybrid Workers in Indonesia - Burhanuddin (Malaqbi Publisher, 2026)
The rapid expansion of flexible work arrangements (FWAs) has transformed work-life balance (WLB) dynamics in Indonesia’s digital economy. Although previous studies have primarily emphasized quantitative outcomes, limited research has explored the lived experiences of remote and hybrid workers. This study aims to examine how Indonesian workers negotiate professional and personal boundaries within digitally mediated work environments. Using an existential-hermeneutic phenomenological approach, data were collected through semi-structured interviews with 15 workers from the education, technology, and creative sectors and analyzed using Braun and Clarke’s (2006) reflexive thematic analysis. The findings identified five major themes: blurred work-life boundaries, digital fatigue, flexible productivity, family interference, and coping strategies. The study reveals that WLB is a dynamic process shaped by hyper-connectivity, socio-cultural expectations, gender roles, and sandwich-generation pressures. The findings contribute to Boundary Theory and Conservation of Resources Theory by contextualizing WLB within Indonesia’s collectivist culture and highlighting the importance of organizational support, including healthier digital boundaries and employee well-being policies.